Making and breaking the grid a graphic design layout workshop - Samara, Timothy (Gloucester, MA Rockport Publishers, 2005)
For designers working in every medium, layout is arguably the most basic, and most important, element. Effective layout is essential to communication and enables the end user to not only be drawn in with an innovative design but to digest information easily.Making and Breaking the Grid is a comprehensive layout design workshop that assumes that in order to effectively break the rules of grid-based design, one must first understand those rules and see them applies to real-world projects.Text reveals top designers work in process and rationale. Projects with similar characteristics are linked through a simple notational system that encourages exploration and comparison of structure ideas. Also included are historical overviews that summarize the development of layout concepts, both grid-based and non-grid based, in modern design practice.
Thoughts on structure : an introduction -- Using this book -- Making the grid. Coming to order: a brief history of the grid in modern graphic design -- Grid basics: a workshop in structural designing -- Exhibits: grid-based design projects -- Breaking the grid. Historical interlude: the seeds of deconstruction -- Exploring other options: a guide to grid deconstruction and nonstructural design approaches -- Exhibits: grid deconstructions and non-grid-based projects --Appendices.
Includes bibliographical references (page 207) and index.
Keywords: Grids (Typographic design).; Layout (Printing).; Electronic books